Aplicação do método histórico-gramatical em Lucas 4,16-21 - Coelho, Lázara Divina (2021)
The object of this thesis is the Historical-Grammatical Method in two aspects: first, its formulation, then its applicability to a specific biblical text. It aims to demonstrate the scientific character of the Method and prove its applicability. The working hypothesis is that the Historical-Grammatical Method has a theoretical and methodological instrument capable of developing the interpretation of the biblical text. The theoretical framework is integrated by Bunge's epistemology, Augustine's principle of biblical selfinterpretation and Ernesti's historical-grammatical reading. The research has a basic and applied purpose, and is developed through a qualitative approach to the problem through bibliographic research. It demonstrates the scientific character of the Method, by reconstructing its history, from its very genesis, in the practices of biblical reading of the first Christians, through its formulation in the philological and historiographical studies of the 18th century, to the current configuration. In this path, the contribution of different areas of knowledge is identified, with the transfer of their principles and lights, for the formulation and development of the Method. The historical-grammatical sense is emphasized as the essence of the Method itself and the historical-grammatical exegesis as its realization. The first chapter applies epistemological assumptions to the Method, and demonstrates its scientific character. It uses the state of the matter to highlight the principle of biblical self-interpretation, as a formal criterion of grammaticalhistorical interpretation. By placing the Method historically, it defines it as a set of doctrinal assumptions and interpretive principles that materialize in special rules and techniques to arrive at the meaning of the text. And he describes it as endowed with considerable theoretical and methodological tools. In the second chapter, the Method is applied in the interpretation of the passage of Luke 4:16-21. The presuppositions, principles and rules then identified are taken as theoretical basis. The text is interpreted grammatically and historically. The meaning of the passage is identified as messianic, its character as the Messiah and its program as extending to humanity in all ethnicities, places and times. The formulation and scientific relevance of the Historic-Grammatical Method is confirmed, as well as its applicability to the interpretation of the biblical text